Lung cancer-associated T cell repertoire as potential biomarker for early detection of stage I lung cancer. (December 2021) - Li, Min; Zhang, Chunliu; Deng, Shichao; Li, Li; Liu, Shiqing; Bai, Jing; Xu, Yaping; Guan, Yanfang; Xia, Xuefeng; Sun, Lunquan; Carbone, David P.; Hu, Chengping
Highlights: Immune microenvironment changes can occur at very low tumor burden, even in stage I lung cancer. Lung cancer-associated TCR (LC-aTCR) is a candidate biomarker for early detection of stage I lung cancer with high sensitivity and specificity. Abstract: Background: Early detection of lung cancer in asymptomatic patients remains challenging, especially for stage I. Considering the substantial interaction with tumor immunogenicity, we hypothesized that lung cancer-associated TCR (LC-aTCR) may serve as potential biomarker in early detection of stage I lung cancer. Methods: Individuals who received low-dose computed tomography (LDCT) screening were enrolled in the study. Surgical tissues and peripheral blood specimens were collected and performed with DNA-based T cell repertoire (TCR) sequencing. The motif-based algorithm was used to deconstruct specific lung cancer-associated TCRs (LC-aTCRs). Results: A total of 146 individuals participating in the real-world LDCT screening project were enrolled in this study, including 52 patients with pathologically-confirmed stage I lung cancer and 94 non-cancer controls. We developed a motif-based algorithm to define 80 LC-aTCRs in the training cohort. Moreover, in the validation cohort, high sensitivity and specificity was showed in stage I lung cancer with 72% and 91% respectively, and the AUC of the ROC curve was 0.91 (95% CI: 0.85 ∼ 0.96). Conclusion: This work provides inspiration for stage I lung cancer detection by using blood TCR profiling data. The combination of TCR-based assay and routine screening deserves further testing in larger cohorts.